Media Framing Analysis in News Making on the Case of Molestation at the Ndholo Kusumo Tahfidzul Qur'an Islamic Boarding School, Pati Regency - Saiful Romadon; Ade Budi Santoso (Journal of Creative Power and Ambition (JCPA), 2026)
This research is entitled "Analysis of Media Framing in Making News on the Case of Molestation at the Ndholo Kusumo Tahfidzul Qur'an Islamic Boarding School, Pati Regency". The object of this research is news related to the case of molestation at the Ndholo Kusumo Tahfidzul Qur'an Islamic Boarding School, Pati Regency. The news that became the subject of the research was the online media viva.co.id entitled "Kiai Ponpes Pati Molested Dozens of Students. MUI Angry". This type of qualitative research is descriptive using the Framing Analysis Model of Zhondang Pan and Gerald M. Kosicki as an analysis technique. The results of this study indicate that the syntactic elements of the headline and lead in the news published by viva.co.id are sufficient to show clarity. Which describes the content of the news related to the MUI's response to the case of molestation at the Ndholo Kusumo Tahfidzul Qur'an Islamic Boarding School. However, the word Kiai in the headline will potentially give rise to negative public perceptions of the title Kiai which allows the creation of stereotypes and reduces public trust and respect for the title Kiai. The script element found that viva.co.id did not meet the 5W+1H news completeness criteria. The "where" section lacks detailed explanation. The thematic structure of the viva.co.id news portal thoroughly describes the news and provides clear information. The rhetorical structure includes the word "alleged" in the first paragraph, suggesting that the news is not entirely accurate. However, in the headline, the author seems to assert that dozens of female students were sexually abused by a religious leader (Kiai). Furthermore, the headline "Kiai of Pati Islamic Boarding School Molested Dozens of Female Students" uses general language, potentially leading to the generalization that Islamic boarding school kiai in Pati Regency sexually abused female students. This would certainly mislead or misunderstand readers if they only read the headline.